Statistical Toolkit for Assessing the Financial Security of Regions - Vladimirovich Dianov, Dmitry; Evgen'evich Suglobov, Alexander; Ivanovna Kuznetsova, Elena; Viktorovna Rusavskaya, Alevtina; Vladimiro, Andrey (International Journal of Engineering and Technology, 2018)
Each stage of the statistical research of economic and financial security requires the use of another extensive block of statistical toolkit represented by methods of general theory of statistics and mathematical statistics, including multidimensional groupings â€“ cluster analysis, correlation and regression methods. This scientific article is devoted to such a statistical toolkit and analytical capabilities for its application in the research into the financial security of the region, where the financial security of the Moscow region, described by a range of financial and economic indicators, is the subject of statistical research.Â Â